International Speaking Engagements - Andrew Beale (2010)
World Trade Organization: 'WTO/WIPO Colloquium for teachers of IP', Geneva, 2010 World Intellectual Property Organization: 'WIPO Forum on Intellectual Property & SMEs for IP Offices of OECD & EU Enlargement Countries' Geneva, 2009‘WIPO – League of Arab States Regional Training Program on Intellectual Property and Management of Innovation by Micro, Small and Medium Sized Enterprises’ Cairo, 2009Co-organized the 'WIPO Forum on Intellectual Property & SMEs for IP Offices of OECD & EU Enlargement Countries' Cardiff, 2008'WIPO Forum on Intellectual Property & SMEs for IP Offices of OECD & EU Enlargement Countries' Geneva, 2007 'WIPO Forum on Intellectual Property & SMEs for IP Offices of OECD & EU Enlargement Countries' The Hague, 2006 'WIPO – WASME Forum on Practical IP Issues for SME Support and Financial Institutions, including Technology/Business Incubators' Geneva, 2005 'WIPO Forum on Intellectual Property & SMEs for IP Offices of OECD & EU Enlargement Countries' Alicante, 2004 European Patent Office: PATLIB: 'Investing in the Future' Liege, 2003 European Commission ‘Sub-Regional Conference on Intellectual Property and the Competitiveness of Small and Medium – sized Enterprises (SMEs) in the Agro-Foods Sector in Latin America’ Guadalajara & Veracruz, 2009 'Innovating through EU Regional Policy' Brussels, 2006'PATINNOVA: Sixth European Congress on Patents – Patents in the digital era & Patents serving entrepreneurship' Cardiff, 2001 Other International Invitations IP Australia (2005) Ministry of Economic Development, New Zealand (2005) Enterprise Ireland (2004)